A retrospective study of oral fractures in cats and dogs presented to Universiti Veterinary Hospital (UVH) from 2010 to 2013 - Teh, Ai Ling (2015)
The medical records and radiograph for dogs and cats that had been diagnosed with oral fractures at Universiti of Veterinary Hospital, Universiti Putra Malaysia between 2010 to 2013 were reviewed retrospectively. 137 of oral fractures cases in 88 cats and four dogs were identified in this study. Patient signalment, clinical signs, types of trauma, locations of fracture, types of fractures, treatment options and complication were noted. The most common locations of oral fracture in both cats (24%) and dogs (50%) were mandibular fractures. A complete and transverse mandibular fracture was the most common fractures type in cats (65%). But in dogs 50% was complete and oblique mandibular fracture. Majority of the cases were brought in due to road traffic accident cats (59%) and in dogs (50%). Most of cases presented with single location fractures (72%). The most common multiple fractures were temporomandibular junction luxation and mandibular fractures (two locations), and mandibular symphysis separation, temporomandibular joint luxation and zygomatic arch fractures (three different locations). Majority of cats (46%) were surgically stabilized compare to dogs (50%) which were stabilized with conventional treatment. The most common surgical approach was cerclage wire repair (62%) in both cats and dogs. Most of cases stabilized surgically has malocclusion (42%). Majority cases stabilized surgically were responded well (50%). However, there were cases stabilized surgically (79%) but died either before the surgery due to severe trauma or after the surgery due to other complication.